The masked city [large type] - Cogman, Genevieve (Cogman, Genevieve. Invisible library novel., 2017)
"The written word is mightier than the sword--most of the time... Working in an alternate version of Victorian London, Librarian-spy Irene has settled into a routine, collecting important fiction for the mysterious Library and blending in nicely with the local culture. But when her apprentice, Kai--a dragon of royal descent--is kidnapped by the Fae, her carefully crafted undercover operation begins to crumble. Kai's abduction could incite a conflict between the forces of chaos and order that would devastate all worlds and all dimensions..."--